Effects of Self-Regulation Theory-Based Education on Psychological Response, Compliance, IDWG, and Perceived Complaints - Arsa, Sandi Alfa Wiga; Erni Setiyorini; Thatit Nurmawati; Kristina Widyanti (Universitas Muhammadiyah Lamongan, 2025)
Introduction: Although hemodialysis is effective in prolonging life expectancy, it often results in physical complaints such as shortness of breath, nausea, headache, edema, and chest pain, as well as psychological complaints including anxiety, depression, and non-compliance with treatment regimens. These issues may ultimately affect therapeutic outcomes, such as increased Interdialytic Weight Gain (IDWG) and other complications. This study aims to analize the effects of self-regulation theory-based education on psychological response, compliance, IDWG, and perceived complaints in hemodialysis patients Methods: This study employed a quantitative approach with a one-group pretest-posttest randomized experimental design. A total of 21 hemodialysis patients from the Hemodialysis Unit were selected as participants. The Wilcoxon test was used to analyze the data. Results: Significant results in Psychological Factors (p = 0.029), Compliance (p = 0.000), IDWG (p = 0.032), and perceived complaints (p = 0.049), the findings demonstrated significant improvements across all measured variables following the implementation of self-regulation-based health education Conclusion: Self-regulation-based health education can effectively enhance self-management in hemodialysis patients by addressing their specific physical and psychological challenges